Technological and philosophical perspectives on photovoltaic electric bicycles for sustainable mobility - Endang Susanti; Azriyenni Azhari Zakri; Antonius Rajagukguk (International Journal of Applied Power Engineering (IJAPE), 2026)
This paper investigates photovoltaic-based electric bicycles (PV e-bikes) as sustainable transportation solutions through integrated technological and ethical analysis. Our systematic literature review and mathematical modeling examine technological advancements, environmental benefits, and implementation challenges. Key findings reveal PV e-bikes can extend travel range by 20.5 km on sunny days and reduce annual grid charging needs by 93% in optimal locations. Advanced perovskite solar cells achieving 25.7% efficiency show promise for revolutionizing on-the-go charging. Mathematical analysis reveals optimal PV panel sizing requires 45-225 W capacity depending on integration approach, with battery technologies ranging from LiFePO₄ (2000-4000 cycles) to advanced lithium-ion systems. However, critical challenges persist including partial shading effects reducing efficiency by 65-82%, weather-dependent performance variations, and initial production costs of $467-900. The study addresses specific gaps in previous research by developing a comprehensive framework integrating technical performance metrics with ethical considerations. Novel contributions include: i) mathematical modeling of PV-battery optimization for e-bike applications, ii) systematic analysis of partial shading mitigation strategies, and iii) philosophical framework addressing social justice implications. Results demonstrate that while PV e-bikes offer significant environmental benefits, their widespread adoption requires addressing technological limitations, cost barriers, and equitable access concerns.